Therapeutic development of group B Streptococcus meningitis by targeting a host cell signaling network involving EGFR - Ningyu Zhu; Chengxian Zhang; Atish Prakash; Zheng Hou; Wei Liu; Weifeng She; Andrew Morris; Kwang Sik Kim (EMBO Molecular Medicine)
Abstract Group B Streptococcus (GBS) remains the most common Gram‐positive bacterium causing neonatal meningitis and GBS meningitis continues to be an important cause of mortality and morbidity. In this study, we showed that GBS penetration into the brain occurred initially in the meningeal and cortex capillaries, and exploits a defined host cell signaling network comprised of S1P2, EGFR, and CysLT1. GBS exploitation of such network in penetration of the blood–brain barrier was demonstrated by targeting S1P2, EGFR, and CysLT1 using pharmacological inhibition, gene knockout and knockdown cells, and gene knockout animals, as well as interrogation of the network (up‐ and downstream of each other). More importantly, counteracting such targets as a therapeutic adjunct to antibiotic therapy was beneficial in improving the outcome of animals with GBS meningitis. These findings indicate that investigating GBS penetration of the blood–brain barrier provides a novel approach for therapeutic development of GBS meningitis.